The new manager's handbook 24 lessons for mastering your new role - Stettner, Morey (McGraw-Hill professional education, 2003)
Explains the rules of being a new manager and gives tips and pointers for teaming with employees while inspiring them to breakthrough performance and results. This book shows the ways to: delegate review performance; think strategically; lead meetings; give and get results-oriented feedback; provide direction; and speak with power.